PLANT COMMUNITY DYNAMIC AT KAWAH PUTIH AND RANCA UPAS RECREATION AREA, WEST JAVA - M. Suleman (NIM : 20695502), Samsurizal
Abstract : A research about plant community dynamic at Kawah Putih and Ranca Upas recreation area, West Java has been done from August 1996 until January 1997. Data sampling in disturbed location (DL) and undisturbed location (UL) at natural forest, planted forest and grasses community using quadrate methods. Vegetation at each location was analyzed based on the canopy layered to compare those structure and species composition and to predict the regeneration ability for several tree species. The vegetation differences level at each location was analyzed based on Bray-Curtis Index of similarity and the diversity was analyzed based on Shannon\'s Index (H\'). Observation of the dynamic and plant Phenology were done only for Vaccinium varingiaefolium population at natural forest and Altingia excelsa at planted forest. Population stability was predicted using Leslie matrix and survival ability was analyzed based on Silvertown formula. Dominant species at each vegetation layer in both locations of natural forest was V. varingiaefolium. The level of vegetation similarity (IS =0.72) and species diversity (DL H\' =2.62 and UL H\' =2.86) in both locations were relatively high. Dominant species in both locations of planted forest was A. excelsa at 1\" and 2nd layer, and Elatostema strigosum at 3rd layer. The level of vegetation similarity (IS =0.50) and species diversity (DL H\' =1.63 and UL H\' =1.61) in both locations were relatively high. Dominant species at grass community was Panicum sp.1 in DL and Panicum sp. 2 in UL. The level of vegetation similarity (IS =0.0) and species diversity (DL H\' =0.83 and UL H\' =1.4) in both locations were relatively low. According to proportion of individual amount per 0.1 ha at each vegetation level, trees species at natural forest that has good regenerated ability in DL three species and in UL five species, and at planted forest in DL one species and in UL five species. Survival ability of V. varingiaefolium and A. excelsa seedlings in UL (Lx =0.70 and 0.66) higher than DL (Lx =0.47 and 0.33). Based on the Leslie matrix analysis, popula tion structure of both speciel were more stable in UL